Those Who Teach Must Also Do: Diversity, Equity and Inclusion in Legal Education and the Canadian Armed Forces - Poon, Michael (McGill GLSA Research Series, 2022)
Diversity, Equity and Inclusion (DE&I) initiatives have become a priority for many organizations within Canada. In legal academia it has become both a procedural and substantive imperative, as it grapples with meaningful integration of these considerations, and appropriate adaptation to current social and technological challenges. This paper sketches selected considerations in implementing DE&I within legal education, and transplants them into Canadian Armed Forces (CAF) engagements with DE&I implementation, with a focus on the transmission of legal norms and values in a non-legal environment and teaching context, using an explicitly socio-legal orientation. Drawing from legal education literature highlighting the challenges and opportunities within the university, and key insights regarding DE&I implementation’s history and current developments within the CAF derived by scholars in a themed-2020 conference, I argue that a process of translation and adaptation of legal education practices and engagement with DE&I into the CAF context will provide valuable insights into both communities of practice and transform and be transformed in the process, in particular with developing key concepts, solidifying abstract concepts and challenges, leveraging case study and simulation techniques, exploiting remote and hybrid pedagogical tools, and furthering legal education engagement outside the academy.